Yuck's amazing underpants : and, Yuck's scary spider - Morgan, Matthew (Simon & Schuster Books for Young Readers, 2012)
Yuck has been wearing his favourite underpants every day and every night for six weeks. Mum wants them in the wash, but Yuck has other plans. With the help of a jar of mould, his underpants are soon taking on a life of their own.